2015
DOI: 10.1007/s00216-015-8670-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics study of polycystic ovary syndrome based on UPLC-QTOF-MS coupled with a pattern recognition approach

Abstract: Metabolomics has become an important tool in distinguishing changes in metabolic pathways and the diagnosis of human disease. Polycystic ovary syndrome (PCOS) is a relatively complicated, heterogeneous endocrine disorder. The etiology and pathogenesis of PCOS remain uncertain. In this study, based on the platform of ultra performance liquid chromatography tandem quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS) and the method of pattern recognition, a comprehensive metabolomics approach has been appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 49 publications
1
54
1
Order By: Relevance
“…The 25(OH)D 2 concentrations measured in PCOS and MetS were indicative of vitamin D deficiency (<20 ng/mL), as defined by the Institute of Medicine (47) and seen in other studies of PCOS (21, 48, 49). Vitamin D deficiency has also been associated with metabolic disturbances such as obesity, insulin resistance, and dyslipidemia (50, 51).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The 25(OH)D 2 concentrations measured in PCOS and MetS were indicative of vitamin D deficiency (<20 ng/mL), as defined by the Institute of Medicine (47) and seen in other studies of PCOS (21, 48, 49). Vitamin D deficiency has also been associated with metabolic disturbances such as obesity, insulin resistance, and dyslipidemia (50, 51).…”
Section: Discussionmentioning
confidence: 63%
“…Escobar-Morreale et al (15) demonstrated that obese women with PCOS had a different profile of fatty acid metabolites suggestive of increased lipolysis compared with nonobese women with PCOS who demonstrated suppression of lipolysis. When comparing obese women with PCOS to nonobese women with PCOS or to BMI-matched controls without PCOS, long-chain fatty acids such as linoleic acid were elevated only in the obese women with PCOS (15); this finding was corroborated by other groups that did not match control groups by BMI (19, 21). The lack of significant differences in the lipid metabolite profile in the current study may be attributable to matching our control group for both obesity and MetS.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Metabolites with a variable importance in the projection (VIP) value >1 by PLS-DA modeling and a P value <0.05 by Student's t-test were considered to be significantly altered (Gao et al, 2013;Dong et al, 2015). The samples were normalized by sum to total peak intensity.…”
Section: Metabolomics Data Analysismentioning
confidence: 99%